Recanalization of refractory benign biliary stricture using magnetic compression anastomosis - Jang, Sung Ill; Rhee, Kwangwon; Kim, Haewon; Kim, Yong Hoon; Yun, Jieun; Lee, Kwang-Hun; Bang, Seungmin; Chung, Jae Bok; Lee, Dong Ki (Endoscopy, 2014)
Background and study aims: Endoscopic or percutaneous treatments are preferentially attempted for benign biliary stricture (BBS). However, these methods are not feasible if a guide wire cannot be passed through the stricture. This study evaluated the usefulness and technical requirements of magnetic compression anastomosis (MCA) in refractory BBS. Patients and methods: MCA was performed in patients with BBS that had not been resolved with conventional treatments. One magnet was delivered through the percutaneous transhepatic biliary drainage tract and the other magnet was advanced through three different routes. After magnet approximation and recanalization, an internal drainage catheter was placed for 6 months and then removed.Results: Seven patients underwent MCA, and recanalization was successfully achieved in five. MCA failure in two cases was attributed to long stenotic segments and parallel alignment of the axes of the magnets. The mean follow-up period after recanalization was 485.2 days. Five patients with successful recanalization showed no MCA-related complications or restenosis. Conclusions: MCA represents an alternative nonsurgical method of BBS recanalization that cannot be treated with conventional methods.